Case reportOmalizumab in the prevention of anaphylaxis during immunotherapy: a case report - Stelmach, Iwona; Sztafińska, Anna; Woicka-Kolejwa, Katarzyna; Jerzyńska, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Omalizumab is approved for the treatment of chronic severe persistent asthma. As a trigger for anaphylaxis, the frequency of subcutaneous specific immunotherapy (SCIT) is high. We report the case of a 11-year-old boy with severe allergic asthma. During the initial phase of immunotherapy he experienced anaphylaxis and SCIT was discontinued. Because of uncontrolled asthma, despite the inhaled steroids and beta agonists were taken into consideration, omalizumab 300 mg once every 4 weeks was initiated. Currently, the maintenance dose has been reached and SCIT is continued without any side effects. The clinical implication of the above case report is that children with severe allergic asthma who are pre-treated with omalizumab might also benefit in the future from SIT as a causal treatment option.